2006
DOI: 10.1002/qsar.200540210
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐Assisted Dimroth Rearrangement of Thiazines to Dihydropyrimidinethiones: Synthetic and Mechanistic Aspects

Abstract: The Dimroth rearrangement of a set of substituted 2-amino-6H-1,3-thiazines into 3,4-dihydropyrimidine-2-thiones was investigated. The rearrangements were carried out under microwave irradiation conditions in batch or continuous flow format, employing either toluene or 1-methyl-2-pyrrolidone as solvent. Thiazines bearing an ester group at the C5 position rearranged at a considerably higher temperature than derivatives without substituents at this position into the corresponding pyrimidinethiones. This strictly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 48 publications
0
39
0
1
Order By: Relevance
“…A more detailed study on this so-called Dimroth rearrangement [33,34] will be reported elsewhere. [35] Interestingly, not only electron-withdrawing but also alkyl R 4 -substituents Scheme 6. Use of chiral inputs in the HWE/aza-DA 4CR.…”
Section: Resultsmentioning
confidence: 99%
“…A more detailed study on this so-called Dimroth rearrangement [33,34] will be reported elsewhere. [35] Interestingly, not only electron-withdrawing but also alkyl R 4 -substituents Scheme 6. Use of chiral inputs in the HWE/aza-DA 4CR.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in a scale-up run, a Fischer indole synthesis was performed resulting in the preparation of 25 g (96%) of 2,3,4,9-tetrahydro-1H-carbazole starting from phenylhydrazine and cylohexanone within 1 h at 200 C using an acetic acid/2-propanol (3:1) mixture as a solvent, thus preventing precipitation of the formed product (Scheme 8). Applying microwave heating to a glass flow cell-a standard 10-mL Pyrex vial filled with sand [20] or with glass beads [21]-the latter synthesis has been previously achieved using somewhat lower temperatures.…”
Section: Five-membered Ring Heterocycles With One Heteroatommentioning
confidence: 99%
“…Using a microwave-heated glass flow cell filled with glass beads, Kappe and coworkers reported on the wellknown multicomponent Biginelli reaction, going from milligram to 25 g/h scale [21]. The standard 10-mL reaction vessel was charged with 2-mm-sized glass beads, thus creating microchannels, which affect the residence time of the reaction mixture in the microwave heating zone (Scheme 43).…”
Section: Six-membered Ring Heterocycles With Two Heteroatomsmentioning
confidence: 99%
“…In a related study, the group of Kappe reported on Biginelli reactions and Dimroth rearrangements comparing batch and CF techniques (Scheme 17) [77]. Similar to the above-mentioned setup, a corresponding CF coil for the CEM Voyager unit was charged with 2 mm-sized glass beads in order to create microchannels, which result in increased residence time of the reaction mixture in the microwave heating zone (Fig.…”
Section: Scheme 12 13-dipolar Cycloaddition Reactions Under Cf Condimentioning
confidence: 99%
“…The described setup was initially evaluated with the well-known Biginelli reaction going from a milligram to a 25 g h -1 scale, and furthermore extended to the microwave-assisted rearrangement of thiazines (Scheme 17). The Biginelli reaction was carried out with equimolar ratios of the building blocks in a concentration of 1.3 M at an adjusted flow-rate of 2 mL min -1 , resulting in an [77] identical residence time compared with the batch attempt. In contrast, the Dimroth rearrangement was performed with a flow-rate leading to an almost doubled residence time of the substrate within the microwave heating zone compared to the batch experiments.…”
Section: Scheme 12 13-dipolar Cycloaddition Reactions Under Cf Condimentioning
confidence: 99%